Transcriptome data reveals the conservation genetics of Cypripedium forrestii, a plant species with extremely small populations endemic to Yunnan, China - Lin, Liewen; Cai, Lei; Huang, Hua; Ming, Shengping; Sun, Weibang (Frontiers in Plant Science, 2024)
The Cypripedium forrestii is an orchid species with extremely small populations (PSESP) in Yunnan, China. C. forrestii is range-restricted and less-studied than many orchid species, and it is exposed to various threats to its survival. We investigated its potential habitats and collected 52 samples from eight locations, as well as two outgroup species for reference. We developed genetic markers (SNPs) for C. forrestii based on transcriptome sequencing (RNA-seq) data, and analyzed the genetic diversity, population structure, gene flow and demographic history of C. forrestii in detail. C. forrestii is a taxonomically independent species to protect. We found that the genetic diversity of C. forrestii was very low (1.7e -4 ) compared with other endangered species.We identified three genetic clusters, and several populations with distinct genetic backgrounds. Most genetic diversity was found within sampling sites (87.87 %) and genetic clusters (91.39 %). Gene flow has been greatly limited over the most recent generations, probably due to geographical distance, historical climate change and habitat fragmentation. We also detected a severe bottleneck event brought about by the recent population constraints. These factors, together with its reproductive characteristics, contribute to the population fragmentation and low genetic diversity of C. forrestii. Based on our findings, we suggest an integrative conservation strategy to protect and recover the genetic diversity of C. forrestii and a further comprehensive study of its ecological traits in the future.